The Professional Dimension in Spanish Prison Socio-Educational Action - Victor Manuel Martín-Solbes; Fanny T. Añaños; Elvira Molina-Fernández; Rubén J. Burgos-Jiménez (MDPI AG, 2021)
(1) Background: The article addresses the reality of prison professionals in ordinary and open prison conditions, which includes the perceptions of women prisoners, due to their low institutional presence that limits their reintegration, from a socio-educational perspective. The aim is to analyse psycho-emotional, educational, and work-related dimensions of professionals and the perception of female prisoners. (2) Methods: The study was carried out with a mixed design from two research projects. The sample consisted of 102 professionals and 75 women from 13 autonomous communities. The instruments were semi-structured questionnaires and interviews with the female prisoners. For the analysis, content analysis, basic statistics, contingency tables, and independence tests were carried out. (3) Results: The results indicate a lower presence of educational professionals and a higher presence of women. Most of them believe more in the reintegration of women, but see ordinary imprisonment and drug consumption as a limitation for it. The professionals state the lack of resources, bureaucratisation, and management, lack of training, and retraining as the main problems and needs. For their part, women demand individualised interventions adapted to their circumstances. (4) Conclusions: In short, it shows a professional reality that can be improved but with strengths such as motivation, experience, and social skills. The socio-educational dimension is valued for the dignification of women prisoners, their transition to life in freedom, and their reintegration.